Analysis of formal and informal networks and the role of internal actors in organizations: a comparative study (Research, Society and Development, 2021)
This work aims to compare the formal and informal networks built in an organization and the role of internal actors involved in this process - employees, using the Social Network Analysis methodology - ARS, within an organization, in order to understand the types formal and informal relationships based on a matrix of quantitative data with the support of the UCINET software. A census survey was carried out of all employees in a company composed of 77 employees with 75 valid cases. Through the extracted quadratic matrix, both formal and informal, density, centrality, reciprocity, clustering and egonet were analyzed, including aspects related to gender and function. The results show differences between the formal and informal sociograms in both the identified variables and related aspects, suggesting that the formal and informal networks have different behaviors, and also suggest the contribution of using the analysis of social networks so that managers can understand the panorama strategic relationship between its employees both in professional involvement and in personal treatment.